2007
DOI: 10.1103/physrevlett.98.210602
|View full text |Cite
|
Sign up to set email alerts
|

Superfluidity versus Anderson Localization in a Dilute Bose Gas

Abstract: We consider the motion of a quasi-one-dimensional beam of Bose-Einstein condensed particles in a disordered region of finite extent. Interaction effects lead to the appearance of two distinct regions of stationary flow. One is subsonic and corresponds to superfluid motion. The other one is supersonic and dissipative and shows Anderson localization. We compute analytically the interaction-dependent localization length. We also explain the disappearance of the supersonic stationary flow for large disordered samp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
93
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(98 citation statements)
references
References 32 publications
5
93
0
Order By: Relevance
“…Nevertheless, a detailed study [490] has shown that expansion of a quasi-2D cloud may lead to weak and even strong localization using currently available speckle patterns. Other works have revealed that Anderson localization may occur during transport processes in repulsive BECs [491][492][493]. In this case, however, and for condensates at equilibrium, the interaction-induced delocalization dominates disorder-induced localization, except for the case of weak interactions [494] (see also earlier work in Ref.…”
Section: Matter-waves In Disordered Potentialsmentioning
confidence: 99%
“…Nevertheless, a detailed study [490] has shown that expansion of a quasi-2D cloud may lead to weak and even strong localization using currently available speckle patterns. Other works have revealed that Anderson localization may occur during transport processes in repulsive BECs [491][492][493]. In this case, however, and for condensates at equilibrium, the interaction-induced delocalization dominates disorder-induced localization, except for the case of weak interactions [494] (see also earlier work in Ref.…”
Section: Matter-waves In Disordered Potentialsmentioning
confidence: 99%
“…A central aim in this context is the realization and unambiguous identification of strong Anderson localization with Bose-Einstein condensates, which was attempted by several experimental groups [1][2][3] with recent success [4,5], and theoretically studied both from the perspective of the expansion process of the condensate [6,7] as well as from the scattering perspective [8,9]. Complementary studies were focused on localization properties of Bogoliubov quasiparticles [10,11], on dipole oscillations in the presence of disorder [12,13], as well as on the realization of Bose glass phases [14,15].…”
mentioning
confidence: 99%
“…The past years have witnessed an increasing number of theoretical and experimental research activities on the behavior of ultracold atoms in magnetic or optical disorder potentials [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. A central aim in this context is the realization and unambiguous identification of strong Anderson localization with Bose-Einstein condensates, which was attempted by several experimental groups [1][2][3] with recent success [4,5], and theoretically studied both from the perspective of the expansion process of the condensate [6,7] as well as from the scattering perspective [8,9].…”
mentioning
confidence: 99%
“…In the case of matter waves, the localization of Bose-Einstein condensates (BEC) is, at present, a very active research topic investigated by several experimental and theoretical groups [1,2,3,4,5,6,7,8], in particular with the recent observation of the (1D) localization of matter waves in a disordered optical potentials [9,10]. Although, in these experiments, the atom-atom interactions were negligible, the basic question remains how effects of interference between multiply scattered waves, such as weak or strong localization, are affected by interactions.…”
mentioning
confidence: 99%